KAMUS DIGITAL JAMAK TAKSIR DALAM PEMBELAJARAN KITABAH BERBASIS TEKNOLOGI DI PERGURUAN TINGGI KEAGAMAAN - Joni Kawijaya; Khabibul Khoiri; Yusuf Mustofa (CV JK Riset Publishing Group, 2025)
Kitabah (writing) instruction in Islamic higher education faces challenges due to the complexity of jamak taksir (broken plurals) and limited digital tool integration. This study evaluates the effectiveness of a jamak taksir digital dictionary in enhancing students' Arabic writing skills. Using a descriptive quantitative approach, data were collected from 20 Arabic Language Education students through Likert-scale questionnaires and observations, then analyzed via SPSS. Results indicate the digital dictionary is highly effective, earning an overall mean score of 4.23 (84.6%), categorized as